PEMBELAJARAN PAI BERBASIS LITERASI DIGITAL DI PONDOK PESANTREN MUHAMMADIYAH QURSAINS WONOGIRI - Afinudin, Ahmad; Sumaryanti , Lilis; Erwahyuddin , Devid (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study is motivated by the need for “pesantren” (Islamic boarding schools) to adapt to advancements in information technology without compromising Islamic values or their distinctive identity. The research aims to describe the implementation of digital literacy-based Islamic Religious Education (PAI) at the Muhammadiyah Qursains Islamic Boarding School in Wonogiri, in response to shifting educational paradigms in the digital era. A qualitative approach utilizing a case study design was employed. Data were gathered through in-depth interviews, observations, and document analysis, involving teachers, students, and school administrators as key informants. The findings indicate that digital literacy-based PAI instruction has been implemented through the use of audio-visual media, Chromebooks, YouTube, Smart TVs, and Islamic software such as Maktabah Syamilah to broaden access to learning resources and enhance student engagement in the learning process.